Development of a Plasmodium vivax biobank for functional ex vivo assays - Rashmi Dash; Kristen M. Skillman; Ligia Pereira; Anjali Mascarenhas; Sheena Dass; Jayashri Walke; Anvily Almeida; Mezia Fernandes; Edwin Gomes; John White; Laura Chery-Karschney; Anar Khandeparkar; et al. (Malaria Journal, 2023)
Abstract Background Plasmodium vivax is the second most prevalent cause of malaria yet remains challenging to study due to the lack of a continuous in vitro culture system, highlighting the need to establish a biobank of clinical isolates with multiple freezes per sample for use in functional assays. Different methods for cryopreserving parasite isolates were compared and subsequently the most promising one was validated. Enrichment of early- and late-stage parasites and parasite maturation were quantified to facilitate assay planning. Methods In order to compare cryopreservation protocols, nine clinical P. vivax isolates were frozen with four glycerolyte-based mixtures. Parasite recovery post thaw, post KCl-Percoll enrichment and in short-term in vitro culture was measured via slide microscopy. Enrichment of late-stage parasites by magnetic activated cell sorting (MACS) was measured. Short and long-term storage of parasites at either − 80 °C or liquid nitrogen were also compared. Results Of the four cryopreservation mixtures, one mixture (glycerolyte:serum:RBC at a 2.5:1.5:1 ratio) resulted in improved parasite recovery and statistically significant (P < 0.05) enhancement in parasite survival in short-term in vitro culture. A parasite biobank was subsequently generated using this protocol resulting in a collection of 106 clinical isolates, each with 8 vials. The quality of the biobank was validated by measuring several factors from 47 thaws: the average reduction in parasitaemia post-thaw (25.3%); the average fold enrichment post KCl-Percoll (6.65-fold); and the average percent recovery of parasites (22.0%, measured from 30 isolates). During short-term in vitro culture, robust maturation of ring stage parasites to later stages (> 20% trophozoites, schizonts and gametocytes) was observed in 60.0% of isolates by 48 h. Enrichment of mature parasite stages via MACS showed good reproducibility, with an average of 30.0% post-MACS parasitaemia and an average of 5.30 × 105 parasites/vial. Finally, the effect of ...